Effects of taurodihydrofusidate, a bile salt analogue, on bile formation and biliary lipid secretion in the rhesus monkey. - Beaudoin, M (1975)
Bile salts play a major role in bile formation and biliary lipid secretion. Sodium taurodihydrofusidate (TDHF), a derivative of the antibiotic fusidic acid, closely resembles bile salts in terms of structure, micellar characteristics, and capacity ot solubilize otherwise insolbule lipids. We have therefore studied the biliary secretion of this bile salt analogue and its influence on bile formation and biliary lipid secretion in primates. Alert, unanesthetized female rhesus monkeys prepared with a total biliary fistula were allowed to reach a steady bile salt secretion rate before each study. In three animals (group I),[14C]TDHF was infused intravenously. Most of the compound was secreted rapidly in bile chemically unchanged. The biliary secretion of this drug produced a twofold increase in bile flow; however, the bile salt output was markedly reduced during the infusion. In spite of this reduction, the phospholipid output remained essentially unchanged whereas the cholesterol output increased almost twofold. In five other animals (group II), the effect of TDHF on the bile salt secretion was further investigated by an intravenous infusion of [14C]taurocholate followed by a combined infusion of [14C]taurocholate and TDHF. When TDHF was added to the infusate, a reduction in the [14C]taurocholate output and a progressive rise in the plasma [14C]taurocholate concentration were observed in each animal. An analysis of the data in both groups indicates that (a) the most likely explanation to account for the decreased bile salt output is that the bile salt analogue, TDHF, interfered with bile salt secretion into the biliary canaliculi; (b) TDHF induces a greater secretion of biliary water than was observed with bile salts, an effect consistent with a stimulation of the bile salt-independent canalicular flow; (c) at similar 3alpha-hydroxysteroid secretion rates TDHF caused a significant increase in cholesterol secretion compared to that induced by bile salt. This finding suggests that TDHF affects cholesterol metabolism or secretion in a way distinct from bile salts. Thus, the solubilization of biliary lipids in mixed micelles, although essential, is only one of the factors which determine their secretion into bile.